Distribution Pattern of Artisan Gastronomy Tourism Location in Bandung City - Fatwa, Mabitha Ratna Nur; Turgarini, Dewi; Pratiwi, Ilma Indriasri (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
The artisan gastronomy tourism sector has the potential to attract and support tourism in the city. This research aims to analyze the distribution pattern of famous eating places in the City and analyze the characteristics of tourists in attracting tourism in Surakarta City. The method applied in this research is descriptive qualitative approach, using primary and secondary data. The sampling technique used is non probability sampling with purposive sampling type. The results of data analysis show that the pattern of distribution of eating places in Bandung City is in groups, with location points scattered around the sate building, as well as adjacent to economic centers, cultural tourism centers, and other centers. Characteristics and attractiveness. Bandung has an influence as a tourism developer that attracts tourists, influenced by technological developments, easy accessibility, and a variety of specialties. In terms of the level of interest in artisan gastronomy places in Bandung, tourists are of the opinionthat artisan gastronomy products in this city are attractive